2013
DOI: 10.1002/jcla.21639
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio Predicts Poor Prognosis in Ischemic Cerebrovascular Disease

Abstract: These findings support the role of N/L ratio as a simple inexpensive and readily available marker of prognosis in acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
128
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 18 publications
7
128
1
2
Order By: Relevance
“…Furthermore, the NLR has been reported to be an independent risk factor for the incidence of AIS in generally healthy populations [2]. In our study, the NLR and the total WBC count were significantly higher in the poor outcome group than in the good outcome group, similar to results reported in other studies [23,24,[32][33][34]. This result remains significant even after adjustment for various potential confounders.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, the NLR has been reported to be an independent risk factor for the incidence of AIS in generally healthy populations [2]. In our study, the NLR and the total WBC count were significantly higher in the poor outcome group than in the good outcome group, similar to results reported in other studies [23,24,[32][33][34]. This result remains significant even after adjustment for various potential confounders.…”
Section: Discussionsupporting
confidence: 90%
“…Lately, the NLR has been reported as an independent predictor of the severity and mortality of acute coronary syndrome [17][18][19][20][21][22][23]. Several studies have supported the hypothesis that the NLR is an independent factor for predicting short-term mortality and unfavorable functional outcome in AIS [23,24,32,34,41]. Tokgoz et al reported that the NLR at the time of hospital admission might be a predictor of short-term mortality independent of infarct volume in patients with AIS [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is used to predict the prognosis of patients with various cancers [10,11], cardiovascular diseases [12,13] and hemorrhagic stroke [14][15][16]. Recently, NLR was used to predict in-hospital mortality [17,18], 90-day mortality [19][20][21] and 90-day poor outcomes (mRS≥3) [4,[21][22][23] in patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%